Silicosis: Mechanisms, Clinical Aspects, and Impacts due to Silica Exposure - Esha, Indi; Afdi, Tania Libristina Ambun Suri; Simatupang, Elvando Tunggul Mauliate (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2024)
Silicosis, an occupational lung disease, has significant mortality rates in Indonesia, as reported by Global Health Grove in 2013. The death rate for silicosis stands at 69.3%, with the typical age at death ranging from 40 to 44 years for men and approximately 80 years for women. The pathogenesis of silicosis begins when respirable crystalline silica (RCS) particles enter the airways. These RCS particles bypass the mucociliary defense mechanisms of the respiratory tract and reach the alveoli. Workers frequently exposed to silica are at high risk of developing silicosis, which significantly impacts morbidity and mortality. The diagnosis of silicosis can follow the seven-step principle for determining occupational diseases. Although silicosis is linked to serious conditions such as tuberculosis, autoimmune diseases, and lung cancer, no effective therapy exists. Treatment remains symptomatic, adjuvant, and supportive. To prevent occupational lung diseases, it is essential to involve the government in policy-making for industrial management and workers.